Konvergenz der Verteilungen von Produkte unabhängiger zufälliger Veränderlicher - Bakštys, A. (Lithuanian Mathematical Journal, 1971)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:А. Бакштис. Сходимость законов распределения произведений независимых случайных величинA. Bakštys. Nepriklausomų atsitiktinių dydžių sandaugų pasiskirstymo dėsnių konvergavimas